2009
DOI: 10.1186/1471-2334-9-83
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of coagulase-negative staphylococcal isolates from blood with reduced susceptibility to glycopeptides and therapeutic options

Abstract: BackgroundCoagulase-negative staphylococci (CoNS) are a major cause of nosocomial blood stream infection, especially in critically ill and haematology patients. CoNS are usually multidrug-resistant and glycopeptide antibiotics have been to date considered the drugs of choice for treatment. The aim of this study was to characterize CoNS with reduced susceptibility to glycopeptides causing blood stream infection (BSI) in critically ill and haematology patients at the University Hospital Tor Vergata, Rome, Italy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 26 publications
8
44
1
2
Order By: Relevance
“…CoNS are now the second most common cause of prosthetic valve endocarditis after S. aureus and one of the most frequent pathogens isolated from deep-seated prosthetic implant infections. 4,5 CoNS have also become one of the most common causes of bacteraemia in immunosuppressed patients. 2 Treatment of CoNS infections can be challenging owing to the frequent presence of foreign materials and increasing antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…CoNS are now the second most common cause of prosthetic valve endocarditis after S. aureus and one of the most frequent pathogens isolated from deep-seated prosthetic implant infections. 4,5 CoNS have also become one of the most common causes of bacteraemia in immunosuppressed patients. 2 Treatment of CoNS infections can be challenging owing to the frequent presence of foreign materials and increasing antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Froggatt et al (1989), 42% of S. haemolyticus isolates were intermediately resistant (MIC 6.25 g/ml) to vancomycin. Kimberly et al (2003) in a study involving 321 coagulasenegative staphylococci, reported that a 3.9% of the CNS isolates had decreased vancomycin susceptibility while Natoli et al (2009) reported a prevalence of 5.4% of CNS with reduced susceptibility to glycopeptides. Del et al (1999) evaluated the antimicrobial susceptibility of 239 CNS isolated from blood samples and reported that all isolates were susceptible to vancomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Glycopeptides have traditionally been considered as the drug of choice in the treatment of infections caused by these organisms. Since the first report of teicoplainin resistance in methicillin-resistance CNS in the USA and UK, the emergence of glycopeptides-resistant CNS in patients treated for long period with vancomycin has been increasingly documented (Aritaka et al, 1997;Smith et al, 1999;Natoli et al, 2009 (Cunnigngham, 1993;Obi et al, 2003). In Limpopo Province, Peltophorum africanum, Carissa edulis, Securidaca spp.…”
Section: Introductionmentioning
confidence: 99%
“…Vankomisin ve teikoplanin, klinisyenlerce metisiline dirençli stafilokok infeksiyonlarının tedavisinde en çok tercih edilen antibiyotiklerdir. Ancak son zamanlarda glikopeptid grubu antibiyotiklere duyarlılığı azalmış kökenler bildirilmektedir [8][9][10][11] . Asaad ve arkadaşları vankomisin, daptomisin ve teikoplanine direnç oranlarını sırasıyla %98.7, %98.7 ve %93.3 olarak bildirmişlerdir [10] .…”
Section: İstatistiksel Analizunclassified